2009
DOI: 10.1038/ng.379
|View full text |Cite
|
Sign up to set email alerts
|

HLA-B*5701 genotype is a major determinant of drug-induced liver injury due to flucloxacillin

Abstract: Drug-induced liver injury (DILI) is an important cause of serious liver disease. The antimicrobial agent flucloxacillin is a common cause of DILI, but the genetic basis for susceptibility remains unclear. We conducted a genome-wide association (GWA) study using 866,399 markers in 51 cases of flucloxacillin DILI and 282 controls matched for sex and ancestry. The GWA showed an association peak in the major histocompatibility complex (MHC) region with the strongest association (P = 8.7 x 10(-33)) seen for rs23950… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
684
3
6

Year Published

2009
2009
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 949 publications
(706 citation statements)
references
References 36 publications
13
684
3
6
Order By: Relevance
“…These genotyped patients carried HLA DRB1-03 and/or DRB1-13, known to be associated with autoimmune disease, [19,20]. Although the genotype was not performed in all patients, we can speculate that HLA II class type DR/DQ carried by our patients could explain the role of genetic susceptibility to nimesulide, other xenobiotics, as has been recently demonstrated for both HLA I, and II classes to beta-lactams [21][22][23]. Taken together, these data strengthen a previous hypothesis of autoimmune pathogenesis, in which several environmental triggers generate different epitopes, each to be presented by the different HLA-DR molecules [19].…”
Section: Discussionmentioning
confidence: 58%
“…These genotyped patients carried HLA DRB1-03 and/or DRB1-13, known to be associated with autoimmune disease, [19,20]. Although the genotype was not performed in all patients, we can speculate that HLA II class type DR/DQ carried by our patients could explain the role of genetic susceptibility to nimesulide, other xenobiotics, as has been recently demonstrated for both HLA I, and II classes to beta-lactams [21][22][23]. Taken together, these data strengthen a previous hypothesis of autoimmune pathogenesis, in which several environmental triggers generate different epitopes, each to be presented by the different HLA-DR molecules [19].…”
Section: Discussionmentioning
confidence: 58%
“…86 In a GWAS study, Daly et al in a European cohort found an 80 fold increased risk in susceptibility to flucloxacillin hepatotoxicity in the presence of HLA-B*5701. 88 This drug is widely available in Europe and 5% of the population carry this haplotype. Therefore, generalizability to other population may be an issue.…”
Section: Genetic Factorsmentioning
confidence: 99%
“…17,22 This program has been widely used by researchers and the results generated from the program are already publicized in papers. [22][23][24][25][26][27] Two other ways of verifying the accuracy of the identified CNVs involve comparing the results with the DGV databases in which information on previously reported CNVs is stored, or using another CNV identification program to compare the results with.…”
Section: Resultsmentioning
confidence: 99%